West Nile Virus Central Nervous System Infection in Patients Treated With Rituximab: Implications for Diagnosis and Prognosis, With a Review of Literature. (19th September 2015) - Morjaria, Sejal; Arguello, Esther; Taur, Ying; Sepkowitz, Kent; Hatzoglou, Vaios; Nemade, Ajay; Rosenblum, Marc; Cavalcanti, Marcela S.; Palomba, M. Lia; Kaltsas, Anna
Abstract: The spectrum of West Nile virus (WNV) infection continues to be elucidated. Many cases of WNV are asymptomatic; however, in immunocompromised patients, symptoms are more likely to be severe. We describe fatal WNV central nervous system disease in lymphoma patients who received rituximab, blunting the inflammatory response and complicating diagnosis.